(untitled) (Sebha University Conference Proceedings, 2025)
The increasing prevalence of composite materials can be attributed to their exceptional specific strength, making them a superior alternative to many traditional materials. However, the high cost associated with synthetic fibers poses a significant challenge to the widespread adoption of composite materials across various applications. This challenge has redirected research efforts toward the exploration of natural fibers, which offer a promising solution for the integration of composite materials in numerous industries such as furniture, flooring, decoration, and more. This study focuses on natural composite materials derived from Libyan almond shells. The research examines three different particle sizes of ground almond shells: large granules, medium-sized particles, and fine powder. These ground shells were combined with polyester resin in four distinct ratios: 80:20, 60:40, 40:60, and 20:80. To assess the mechanical properties of the resulting composites, three primary tests were conducted: impact testing, tensile testing, and bending testing. The findings revealed that the samples incorporating almond shell powder exhibited the best mechanical performance across all three tests. Building on the previous research, this study also includes machinability tests on all types of fabricated samples. Several machining operations were performed, including cutting, drilling, hammering, threading, and jointing. These operations were also conducted on comparable samples made from compressed wood, with identical dimensions to the composite material samples, to facilitate a direct comparison of results.